Preparation and Characterization of Natural Rubber/Bentonite Nanocomposites - Al-Khawaldeh, Mohammad Hussein (2004)
Natural rubber/bentonite nanocomposites were prepared from deproteinised natural rubber (dp-NR) and modified bentonite clay by both solvent casting and blending methods. To prepare the nanocomposites by the solvent method, the rubber was first dissolved in toluene and then mixed by stirring with the modified clay at room temperature. In the blending method, the rubber was first softened for 1 minute in an internal Haake mixer and then blended with the modified clay at 60ºC. Modification of the clay by replacing the clay’s sodium ions with alkylammonium (cetyltrimethylammonium (CTA), dodycelammonium (DDA) and octadecylammonium (ODA)) groups was carried out through an ion-exchanger process. Elemental analysis indicated that 0.59 mmol of CTA, 0.75 mmol of DDA and 0.98 mmol of ODA were sorbed by 1 g of the clay. FTIR spectra of the modified clays showed a peak at about 3000 cm-1, which indicated the presence of the amine group stretching. The increase in the degradation temperature of DDA, CTA and ODA in the organobentonite implied that there was a strong intermolecular interaction between the alkylammonium ions and the bentonite. The nanocomposites produced were characterized by XRD and TEM. It was found the nanometer-scale silicate layers of organoclay were completely exfoliated in dp-NR if the organoclay concentration in the composites was less than 1%. However, increase the clay contents to 3% or higher, produced intercalated nanocomposites. The mechanical properties obtained were found to be affected strongly by the organoclay content and the type of alkylammonium groups. Tensile properties of the nanocomposites prepared using the ODA treated bentonite is better than that of the nanocomposites pretreated with the other alkylammonium groups. In addition, mechanical properties of the nanocomposites also effected by the method of their preparation. The solvent casting technique improved several mechanical properties of the nanocomposites compared with those of the nanocomposites produced by the blending method.